(untitled) (The Journal of Building and Land Development, 2023)
Plastic wastes generated at households, institutions, industries and commercial establishments, present contemporary environmental problems in Tanzania. The study aimed at establishing an alternative disposal for Polyethylene Terephthalate (PET) as a stabilizer for subgrade layer in road construction. Laboratory tests were conducted on both un-stabilized and stabilized soil samples. Classification tests were conducted for un-stabilized soil sample only. Compaction and strength tests were conducted on both un-stabilized and stabilized soil samples. Results indicated that un-stabilized sample had 45.6% liquid limit, 28.6% passing 75Âµm sieve and 22.7% plasticity index, hence the sample fell under group classification A-2-7, whose general rating as a subgrade layer was poor. The un-stabilized soil had 9.4% optimum moisture content, 1892 kg/m3 dry density and CBR value of 6. Stabilized soil sample with 1% PET by weight of soil had 9.1% optimum moisture content, 1873 kg/m3 dry density and CBR value of 16. The 1% stabilized soil sample whose resistance to standard load was 3.1565 kN compared to 1.1235 kN of un-stabilized soil sample. The 1% ratio was equivalent to 21.375 tons of shredded PET plastic waste. These results indicate a potential for PET plastic waste recycling for improving strength of â€œproblem soilsâ€ via mechanical stabilization and thus alternative disposal method for plastic waste hence environmental protection and sustainability.